2017
DOI: 10.1038/srep40307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant species richness on 13C assimilate partitioning in artificial grasslands of different established ages

Abstract: Artificial grasslands play a role in carbon storage on the Qinghai–Tibetan Plateau. The artificial grasslands exhibit decreased proportions of graminate and increased species richness with age. However, the effect of the graminate proportions and species richness on ecosystem C stocks in artificial grasslands have not been elucidated. We conducted an in situ13C pulse-labeling experiment in August 2012 using artificial grasslands that had been established for two years (2Y), five years (5Y), and twelve years (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Studies have found that moderate grazing positively affects soil carbon input (Hafner et al, 2012). The carbon in wastelands is redistributed more proportionately and lasts longer than that in grasslands (Xu et al, 2017). Through studying the vegetation‐soil carbon allocation in different permafrost regions, we found that the 13 C excess in the wetlands exhibited a trend of leaf > root > soil (Figure 4), which is consistent with the results for cereals, forages, and poplars (Liu et al, 2019; Liu et al, 2020; Orgogozo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have found that moderate grazing positively affects soil carbon input (Hafner et al, 2012). The carbon in wastelands is redistributed more proportionately and lasts longer than that in grasslands (Xu et al, 2017). Through studying the vegetation‐soil carbon allocation in different permafrost regions, we found that the 13 C excess in the wetlands exhibited a trend of leaf > root > soil (Figure 4), which is consistent with the results for cereals, forages, and poplars (Liu et al, 2019; Liu et al, 2020; Orgogozo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Through studying the vegetation‐soil carbon allocation in different permafrost regions, we found that the 13 C excess in the wetlands exhibited a trend of leaf > root > soil (Figure 4), which is consistent with the results for cereals, forages, and poplars (Liu et al, 2019; Liu et al, 2020; Orgogozo et al, 2019). Another study conducted 13 C pulse experiments on artificial grasslands of different ages and found that the soil 13 C recovery rates were higher and the average residence time was longer in older grasslands, indicating that species richness has a greater impact on ecosystem carbon storage (Xu et al, 2017). The maximum 13 C excess of the plants in the different permafrost regions occurred in Mohe, and the migration to the roots was the largest (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation